2012
DOI: 10.4196/kjpp.2012.16.5.349
|View full text |Cite
|
Sign up to set email alerts
|

CTLA-4-Tg/CD-28-KO Mice Exhibit Reduced T Cell Proliferationin vivoCompared to CD-28-KO Mice in a Graft-versus-host Disease Model

Abstract: Activated T cells express inhibitory receptors such as CTLA-4 that can downregulate immune responses. Blockade of or genetic deficiency in CTLA-4 can result in autoimmunity. Therefore, strategies to increase the inhibitory function of CTLA-4 may be attractive in settings of undesirable T cell responses such as autoimmunity or transplant rejection. We have tested the hypothesis that transgenic constitutive expression of CTLA-4 can further attenuate immune responses when compared with normal inducible expression… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
5
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 28 publications
1
5
0
Order By: Relevance
“…T cells are associated with the pathogenesis of acute GVHD, and CTLA-4 could alleviate the degree of acute GVHD by regulating T cells, as has been confirmed in previous experiments [16,17]. In the present study, CTLA-4 plasma levels and relative levels were lower in the patients with acute GVHD compared with the healthy controls, and levels were significantly elevated after 28 days of treatment.…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…T cells are associated with the pathogenesis of acute GVHD, and CTLA-4 could alleviate the degree of acute GVHD by regulating T cells, as has been confirmed in previous experiments [16,17]. In the present study, CTLA-4 plasma levels and relative levels were lower in the patients with acute GVHD compared with the healthy controls, and levels were significantly elevated after 28 days of treatment.…”
Section: Discussionsupporting
confidence: 90%
“…In the humanized mice model of acute GVHD, CD8 hi -Treg cells induced in vitro could alleviate GVHD by reducing alloreactive T cell proliferation, as well as decreasing inflammatory cytokine secretion in target organs through a CTLA-4edependent mechanism [16]. Transgenic expression of CTLA-4 in mouse T cells in a murine model of acute GVHD inhibited the proliferation of T cells and thereby reduced the severity of acute GVHD in mice [17]. Nevertheless, the mechanism of CTLA-4 in regulating acute GVHD remains unknown.…”
Section: Introductionmentioning
confidence: 99%
“…It has previously been demonstrated that TIRC7 levels in patients with acute GVHD were higher than healthy controls, and were also markedly declined following treatment, suggesting that TIRC7 level may be an indicator to evaluate the response of patients with acute GVHD to treatment (8). It has been demonstrated that CTLA-4 may play a negative role in the regulation of acute GVHD (6,7). The present study also demonstrated that CTLA-4 may be involved in the pathogenesis of acute GVHD, and that it may downregulate Th1 cell levels by increasing the expression of STAT3 in acute GVHD (19); meanwhile, other studies have reported that TIRC7 is the upstream regulatory molecule of CTLA-4 (9,11).…”
Section: Discussionmentioning
confidence: 99%
“…Peripheral blood mononuclear cells were isolated from patients with acute GVHD using Ficoll-Paque Plus (Sinopharm Chemical Reagent Co., Ltd.). For each experiment, 1x10 7 cells/ml were resuspended in RPMI-1640 medium (Gibco; Thermo Fisher Scientific, Inc.) supplemented with 10% fetal calf serum (Gibco; Thermo Fisher Scientific, Inc.). CD4 + T lymphocytes were purified with negative selection using magnetic beads according to the manufacturer's protocol (Miltenyi Biotec, Inc.), and then CD4 + T cells were generated by stimulation with anti-CD3 and anti-CD28 Dynabeads (Invitrogen; Thermo Fisher Scientific, Inc.) for 3-7 days.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation